Interactions of Na+, K+, Mg2+, and Ca2+ with benzene self-assembled monolayers - Rimmen, M (Langmuir : the ACS journal of surfaces and colloids, 2014)
Interactions between cations and organic molecules are found throughout nature, from the functionality and structure of proteins in humans and animals to the exchange of ions in minerals in soil and oil reservoirs with the fluid phases. We have explored the behavior of the s-block elements that are most common in the natural world, namely, Na(+), K(+), Mg(2+), and Ca(2+). Specifically, we investigated how these ions affect the interactions between surfaces covered by self-assembled monolayers (SAMs) terminated with benzene molecules. We used a flat oxidized silicon substrate and an atomic force microscopy (AFM) tip that were both functionalized with 11-phenoxyundecane-1-thiol and measured the adhesion force between them in solutions of each of the four chloride salts. We observed that the adhesion increased in the order of the Hofmeister series: K(+) < Na(+) ≈ Mg(2+) < Ca(2+). Supplementary evidence from X-ray photoelectron spectroscopy (XPS) allowed us to conclude that K(+) binds in the benzene layers, creating a positive surface charge on the benzene-covered surfaces, thus leading to lower adhesion in KCl solutions than in pure water. Evidence suggested that Ca(2+) does not bind to the surfaces but forms bridges between the layers, leading to higher adhesion than in pure water. In Na(+) and Mg(2+) solutions, adhesion is quite similar to that in pure water, indicating a lack of interaction between these two ions and the surfaces, or at least that the interaction is too weak to be detected by our measurements. The results of our studies clearly show that even a nonpolar, hydrophobic molecule, such as benzene, has a role to play in the behavior of aqueous solutions and that it interacts differently depending on which ions are present. Even ions from the same column in the periodic table behave differently